2014
DOI: 10.1590/0103-6440201302308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nonsurgical Periodontal Treatment on the Alveolar Bone Density

Abstract: The aim of this study was to evaluate the effects of nonsurgical periodontal treatment on alveolar bone density (ABD) and bone height (BH) using direct digital radiography. Nineteen patients (mean age: 36±7.3 years) with generalized chronic periodontitis were examined at baseline, 90 (90AT) and 180 (180AT) days after nonsurgical periodontal therapy. Radiographs were taken from two sites with specific characteristics: 39 sites with probing pocket depth (PPD)≤3 mm and clinical attachment level (CAL)≤1 mm (shallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…These results are consistent with a research conducted by Barros, et al who figured out that there was an increase in alveolar bone density 90 and 180 days after non-surgical treatment. 17 These results are also in accordance with research by Salim, et al, on the effects of scaling and root planning on alveolar bone density and on the number of Porphyromonas gingivalis and Treponema denticule. Salim pinpointed that there was an increase in bone density radiographically before and after scaling and root planning treatments.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with a research conducted by Barros, et al who figured out that there was an increase in alveolar bone density 90 and 180 days after non-surgical treatment. 17 These results are also in accordance with research by Salim, et al, on the effects of scaling and root planning on alveolar bone density and on the number of Porphyromonas gingivalis and Treponema denticule. Salim pinpointed that there was an increase in bone density radiographically before and after scaling and root planning treatments.…”
Section: Discussionsupporting
confidence: 91%
“…The primary goal of periodontitis treatment is to control the infection and inflammation, halt the periodontal tissue destruction, and prevent alveolar bone loss. Removal of microbial biofilms and suppression of inflammation by initial periodontal therapy may block the periodontal tissue degradation; however, only limited regeneration of lost tissues occurs, especially the dental alveolar bone 7 - 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of periodontal disease has been primarily directed towards a microbiological etiology. 25 34 35 36 37 38 Prevention of bone loss by modulating the host response to infection could be a new adjunctive method for the management of PD. 39 40 Apart from maintenance of a meticulous oral hygiene, several studies have indicated that estrogen therapy builds up mandibular bone mass and diminishes the severity of periodontal disease in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%